Cooperation – a special survival strategy for economic organizations in the biotech-pharmaceutical industry - Domonkos, Dávid; Hronszky, Imre (REGIONAL AND BUSINESS STUDIES, 2010)
Medical biotechnology is used by two main types of companies. First, large companies, such as large pharmaceutical companies („big pharma”), which draw on a long history in the given field and develop into more and more innovative biotechnology users. Second, modern biotechnological companies, from which the above mentioned large companies purchase knowledge, projects or services. In terms of developing and spreading technology, small biotech companies often play an important mediating role between science and industry. They provide technology-platforms, knowledge, services for larger companies, such as international pharmaceutical companies or enterprises in the food processing industry. The volume and complexity of biotech and pharmaceutical projects grew in relation to the amount of available information and acquired knowledge. This placed further emphasis on cooperations, and sharing of costs and risk. Due to the risk associated with biotechnology, the complexity of and adherence to rules and the amount of funds, companies were forced to cooperate. First, the necessary monetary tools are available only at the largest companies. Second, the necessary competencies are often missing, because no matter whether a smaller company is market leader in R+D, when it still does not have the necessary experience for production, not even the knowledge for clinical testing. As a consequence, cooperation is necessary to fill these gaps.